AB1062 Gout: Clinical pattern at first evaluation, changes in the last 15 years. (23rd January 2014) - Vazquez Mellado, J.; Hernandez Cuevas, C.; Estrada, E.; García, R.
Abstract : Background: Younger age at onset and higher frequency of severe gout has been reported in some countries (1-3), when compared to previous reports. It seems that these patterns could be changing in the last years. Objectives: To compare the clinical pattern of gout patients attended for the first time, in the same Rheumatology department, during the last 15 years. Methods: Our Gout clinic receives 6-8/new patients each month, they had been evaluated by the same investigators in the last 15 years. We analyzed 568 gout patients from 3 groups: G1: n=316, (1995-2000) (3), G2: n=133m (2006-2007), G3: n=119 (2010-22). Variables: Demographic, clinical, biochemical and functional data regarding gout and associated diseases. Socioeconomic level according to Giuscaffre index; low educational level (<6 years); severe tophaceous gout (>10 tophi); renal failure (Creatinine clearance: <50 mL/min). Hypertension, obesity and hypertriglyceridemia (according to ATPIII criteria definitions). Statistical analysis: t test, ANOVA, chi square and logistic regression. Results: Data from the 3 groups: Males: 97%, age at evaluation: 50.01±12.93 and age at onset: 37.6±13.1 years. In the last 15 years, several demographic, clinical variables and previous treatment had significant changes. Main characteristics are shown in the table as percentages. Conclusions: Although some social and clinical characteristics improved in the last 15 years (socioeconomic and educational level, severe tophaceous gout, renal failure and obesity). We attend now patients younger at onset, with higher frequency of familial gout, hypertension and functional impairment. References: Tanaka E, Yamanaka H, Shoji A, et al. Recent trend in the onset age of gouty arthritis in Japan. Gout and Nucleic Acid Metabolism 2004; 28:7–11. Chen SY, Chen CL, Shen ML, Kamatani N. Trends in the manifestations of gout in Taiwan. Rheumatology (Oxford) 2003; 42:1529–1533. Vazquez-Mellado J, Cruz J, Guzman S, Casasola Vargas J, Lino L, Burgos Vargas R. Severe tophaceous gout. Characterization of low socioeconomic patients from México. Clin Exp Rheumatol 2006;24:233-238. Disclosure of Interest: None Declared